2012
DOI: 10.1377/hlthaff.2012.0490
|View full text |Cite
|
Sign up to set email alerts
|

The Promise And Peril Of Accountable Care For Vulnerable Populations: A Framework For Overcoming Obstacles

Abstract: Accountable care organizations (ACOs) are a promising payment model aimed at reducing costs while also improving the quality of care. However, there is a risk that vulnerable populations may not be fully incorporated into this new model. We define two distinct vulnerable populations, clinically at-risk and socially disadvantaged, and we discuss how ACOs may benefit each group. We provide a framework to use in considering challenges for both vulnerable patients and health systems on the path to accountable care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 14 publications
5
79
0
Order By: Relevance
“…These findings are consistent with concerns that Medicare ACO programs may not effectively address health disparities. 3,4 Because ACO programs are likely to be dominated by currently eligible rather than newly integrated provider groups, 31 the sociodemographic differences between patients served by larger and smaller groups suggest that any clinical benefits achieved by ACOs may accrue disproportionately to white patients in more affluent areas. Previous research [11][12][13][14][15][16] and ACO program requirements 2,32 suggest that provider integration encouraged by ACO programs might be associated with enhanced abilities to monitor and improve quality of care, but we found that larger provider groups achieved smaller racial disparities in only two of six quality measures we analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with concerns that Medicare ACO programs may not effectively address health disparities. 3,4 Because ACO programs are likely to be dominated by currently eligible rather than newly integrated provider groups, 31 the sociodemographic differences between patients served by larger and smaller groups suggest that any clinical benefits achieved by ACOs may accrue disproportionately to white patients in more affluent areas. Previous research [11][12][13][14][15][16] and ACO program requirements 2,32 suggest that provider integration encouraged by ACO programs might be associated with enhanced abilities to monitor and improve quality of care, but we found that larger provider groups achieved smaller racial disparities in only two of six quality measures we analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 The most vulnerable populations experience social disadvantages and clinical vulnerabilities that can result in a disproportionate risk of not receiving the care that they need. 9 In California, safety-net clinics provide health care services to individuals and their families regardless of a patient's ability to pay. 10 Safety-net services are intended to ensure that individuals who are medically underserved and uninsured and living below poverty level receive adequate health care.…”
Section: Introductionmentioning
confidence: 99%
“…The Commonwealth Fund has supported a variety of activities, including a policy analysis of the challenges for vulnerable populations under the accountable care model, 11 a survey of hospitals' ACO activities, 12 an ongoing evaluation of the Alternative Quality Contract in Massachusetts, 3,4 and work by Dartmouth and the University of California, Berkeley, 13 to identify the challenges to implementing a comprehensive approach to evaluation and find ways to address them.…”
mentioning
confidence: 99%